Design, fabrication and anti-aging behavior of a multifunctional inorganic–organic hybrid stabilizer derived from co-intercalated layered double hydroxides for polypropylene. Issue 9 (13th August 2019) - Zhang, Qian; Guo, Yixuan; Marek, Adam A.; Verney, Vincent; Leroux, Fabrice; Tang, Pinggui; Li, Dianqing; Feng, Yongjun
Abstract : The concomitant presence of HALS/DBHP co-intercalated within the LDH structure strongly improved the anti-aging performance of PP, which opens the pathway for potential future research of high-performance PP associated with hybrid fillers. Abstract : It is of great and increasing interest to develop multifunctional additives to enhance the anti-aging performance of polypropylene (PP) and then enlarge its application fields. Here, a hindered amine light stabilizer (H for HALS) and a hindered phenolic antioxidant (D for DBHP) with low molecular weight were co-intercalated into layered double hydroxides (LDHs) through a coprecipitation method to produce a series of inorganic–organic hybrid materials Zn2 Al-H x D y -LDH, adjusting the anion ratio ( x + y = 1 and x  :  y = 0 : 1, 1 : 0, 1 : 1, 2 : 1, 1 : 2). Subsequently, hybrid material LDH fillers (HALS-LDH, DBHP-LDH, H x D y -LDH, and (H-LDH) x (D-LDH) y ), used as anti-aging agents, were successively dispersed into PP by two methods: solvent mixing/casting and extrusion mixing. The corresponding crystalline structure, morphological, rheological properties and thermal and light oxidative degradation behaviour were carefully investigated using various techniques such as XRD, TEM and rheology. The results showed that the LDH fillers were well dispersed into PP without any influence on its crystallization behavior and provided a chain extension effect on PP, and this is even more pronounced for H x D y -LDH. The thermal stability of H x D y -LDH/PP composites ( x  :  y = 1 : 1, 2 : 1, 1 : 2) is significantly improved, compared with that of other composites. Moreover, through the accelerated aging test, the co-intercalated hybrid material H x D y -LDH significantly inhibited the oxidative degradation of PP (thermal-aging and light-aging). The concomitant presence of HALS/DBHP co-intercalated within the LDH structure strongly improved the anti-aging performance of PP. Therefore, such a co-intercalated I/O hybrid adaptive system as a multifunctional additive agent opens the pathway for potential future research of high-performance PP associated with hybrid fillers.